A comparison of numerical methods for damage index based residual ultimate limit state assessment of grounded ship hulls. (March 2022) - Li, Shen; Kim, Do Kyun
Abstract: Considerable efforts have been devoted to developing rapid methodologies for predicting the residual strength of ship hull girders for a given damage scenario (e.g., R–D diagram). This task is usually challenged by the difficulty of a proper definition of damaged scenarios, which is a function of the damage location and extent. The concept of damage index (DI) was proposed to resolve this issue, and its application has been demonstrated previously through the incorporation of the Intelligent Supersize Finite Element Method (ISFEM) and Modified Paik–Mansour (P–M) approach. Alternatively, a Smith-type progressive collapse can be adopted. In fact, this may enable a more comprehensive application of the DI concept, as the Smith-type approach is codified in the Common Structural Rule (CSR) for assessing the longitudinal strength of the hull girder. In light of this, the damage index based assessment tools (i.e., R–D diagram) incorporated with a Smith-type progressive collapse method is presented in this paper. This also facilitates a comparison with the R–D diagram previously developed by ISFEM and Modified P–M approach. Discussion is given regarding the discrepancy between different methods, and recommendations for future research are outlined. Highlights: Damage index (DI) based condition assessment of grounded hull girders. Residual strength versus damage index diagram is developed for the first time by a Smith-type method. Comparison is presented for R-D diagram based on ISFEM, Modified P-M method and Smith method.